WHY ENGLISH IS BECOMING A GLOBAL LANGUAGE? (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
This article examines the reasons why English has become a global language. It highlights historical factors, such as the expansion of the British Empire, which spread English to colonies around the world. The influence of the United States in culture, economy, technology, and education is also analyzed, showing how American media, multinational companies, and top universities contributed to the global spread of English. Furthermore, the article discusses the role of English in science, technology, and international communication, emphasizing its importance in research, programming, online learning, diplomacy, tourism, and business. The study concludes that English has become a key language connecting people from different countries and cultures, making it essential in today’s interconnected world.